The influence of past experiences on the activity of tutor teachers in training - Descoeudres, Magali (Frontiers in Education, 2024)
This research focuses on the activity of six tutor teachers in training involved in the curriculum of primary student-teachers at the University of Teacher Education in Lausanne, in Switzerland. The post-lesson interviews managed by these tutor teachers in training show that their activity is influenced from past experiences lived as student-teachers and from the training they are following. This research aims to understand and analyse the origin from the tools used to mentor their student-teacher during the post-lesson interviews. The theoretical framework uses the concepts of the clinical activity (Clot, 2008) and the method of self and crossed confrontation interviews. Through the real activity of tutor teachers in training, exposed through the methodologies of self-confrontation, our results highlight the influence of past experiences of tutor teachers in training, as well as the nature of the emotionally significant situations they experienced in the past. The influence in their actual activity as tutor teachers in training and which tools they are using from the training are also presented and discussed.